Bioavailability of Nutrients in Seeds from Tropical and Subtropical Soybean Varieties - Moreira, A.; Moraes, L. A. C.; Souza, L. G. M. [UNESP]; Bruno, I. P. (Taylor & Francis Inc, 2016)
The selection of varieties or species of plants with higher nutrient uptake efficiency and nutrient concentration for biofortification of food crops is a key tool to reduce malnutrition. Soybean (Glycine max L. Merr) is one of the most important food crops, because it is consumed directly or indirectly, in the form of seeds, processed (milk and/or derivatives), or used as a protein component of animal feed worldwide. In order to select plants with higher nutrients concentration in seeds, 24 soybean varieties for tropical and subtropical conditions and different general features were assessed. There was great variability in photosynthesis rate, chlorophyll content, seed yield (SY), and concentration and uptake of nutrients by seeds between the varieties. Not genetically modified (NGM) crops showed higher nitrogen (N), cooper (Cu), and manganese (Mn) concentration and higher N, potassium (K), Cu, iron (Fe), Mn, and zinc (Zn) uptake, while for genetically modified (GM) crops only calcium (Ca) concentrations were higher. Varieties BRS 284 and BMX Magna RR showed the highest nutrients concentrations in the group with the highest nutrient efficiency. The genetic variability observed among the varieties regarding uptake and translocation of nutrients into seeds allows selecting more promising materials to be used in the biofortification of nutrients in soybean seeds.
Keywords: Biofortification; essential elements; Glycine max; nutrient concentration; nutrients-use efficiency; nutrient uptake